2016
DOI: 10.1021/acs.orglett.6b01460
|View full text |Cite
|
Sign up to set email alerts
|

Hexafluoro-2-propanol-Promoted Intermolecular Friedel–Crafts Acylation Reaction

Abstract: The intermolecular Friedel-Crafts acylation was carried out in hexafluoro-2-propanol to yield aryl and heteroaryl ketones at room temperature without any additional reagents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(48 citation statements)
references
References 57 publications
1
47
0
Order By: Relevance
“…13 C NMR (101 MHz, CDCl3) δ 193.9, 144.6, 138.6, 136.2, 135.8, 135.3, 130.0, 128.5, 127.4, 122.9, 119.7, 21.7. Spectra data matched with the values reported in literature 8.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…13 C NMR (101 MHz, CDCl3) δ 193.9, 144.6, 138.6, 136.2, 135.8, 135.3, 130.0, 128.5, 127.4, 122.9, 119.7, 21.7. Spectra data matched with the values reported in literature 8.…”
supporting
confidence: 85%
“…1a This issue can be partially resolved by the introduction of elec-tron-withdrawing protecting groups, the use of milder Lewis acids (Et2AlCl 6a-b , imidazolium chloroaluminate 6c or ZrCl4 6d ), reaction with nitrilium salts 7 or the use of hexafluoroisopropanol as solvent. 8 Furthermore, the nucleophilicity of the heterocycles can be enhanced by conversion into Grignard or other organometallic reagents, which can then be added directly to electrophiles or used in metal-catalyzed cross-couplings. 9 Recently, direct C-H acylation catalyzed by transition metals has also been reported.…”
Section: Figure 1 Synthetic and Natural Bioactive Compounds With A 2mentioning
confidence: 99%
“…We considered that a bulky pivaloyl group at the C3 position of indoles might also promote C4 and C5 selectivity. With AlEt 2 Cl in dichloromethane (DCM) or just by the use of hexafluoro‐2‐propanol (HFIP) as a solvent, a pivaloyl group can be selectively installed at the C3 position by a Friedel–Crafts acylation process. To begin our investigation, we synthesized the C3‐pivaloyl‐substituted indoles 2 a , 2 a′ , and 2 a′′ [Eq.…”
Section: Figurementioning
confidence: 99%
“…[12] Very recently,AubØ et al reported that HFIP was beneficial for the Friedel-Crafts (F-C) acylation reactions, and HFIP can be recovered for further use. [13] Brønsteda cids could form hydrogen-bonding interactions in HFIP,t hereby catalyzing F-C reactions of highly electronically benzylic alcohols. [14] In light of the strong HBD ability and mild acidity of HFIP,w es peculate that HFIP could enable the de novo construction of nonnatural a-arylated amino ester fragmentsf rom readily available amines,e thyl glyoxylate and electron-rich arenes through the HFIP-promoted nucleophilic addition of electron-rich arenes with the imine intermediates, which could be generated in situ from the corresponding amines and ethyl glyoxylate.T his new method provides facile access to nonnatural amino esters that are fundamentalb uilding blocks in organic synthesis.…”
mentioning
confidence: 99%